2018
DOI: 10.15758/ajk.2018.20.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Activity Tracker & Application Use on Adherence, Metabolic Syndrome Factor and Body Composition in Middle and Senior-Aged

Abstract: PURPOSE The purpose of this study was to investigate effects of activity tracker & application use on adherence, metabolic syndrome factor and body composition of middle and senior-aged. METHODS The subjects of this study were 1,196 middle and senior-aged man and women with health hazard factor. All of subjects divided to two groups, activity tracker & application use group 990(man=492, wom-en=498) was participating in 24 weeks, and control group 206(man=71, women=135) was not in that program. They performed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Thus, by recommending appropriate mobile apps and wearable devices and encouraging their use, this study made it possible for the users to engage in sustained health management. The findings of this study align with those from previous studies that revealed the significance of health trackers and smart apps that are free of time and space limitations for a sustained increase in physical activities [ 30 , 48 ]. Previous recommendation systems were rather one-sided and manager-centered, which made it difficult for users to stay entertained.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, by recommending appropriate mobile apps and wearable devices and encouraging their use, this study made it possible for the users to engage in sustained health management. The findings of this study align with those from previous studies that revealed the significance of health trackers and smart apps that are free of time and space limitations for a sustained increase in physical activities [ 30 , 48 ]. Previous recommendation systems were rather one-sided and manager-centered, which made it difficult for users to stay entertained.…”
Section: Discussionsupporting
confidence: 90%
“…Continuously checking the user’s amount of activity by using activity- and smartphone-based applications can be considered as a measure of confirming the effectiveness of lifestyle and health care. Jee (2017) reported applications to be effective in promoting motivation, and Kim et al (2018) reported that when using activity measurement and smart-based applications to maintain regular physical activity for 23 weeks, 90.65% of males and 91.37% of females showed continuity. The use of mobile devices has a positive effect on self-efficacy by increasing the practice rate of exercising, which is considered to be the factor that can promote continuous participation in exercise.…”
Section: Discussionmentioning
confidence: 99%
“…According to this research, there were no significant statistic difference in blood pressure and fasting plasma glucose, but plasma triglyceride of LPAG was higher than HPAG, and HDL-C of HPAG was higher than LPAG. Lee et al [18][19][20] showed that HPAG had positively affect to the risk factors The advanced research about alcohol consumption showed that HDL-C of high drinking group was significantly lower than moderate drinking group, and fasting plasma glucose, blood pressure, plasma triglyceride, and waist circumference were high enough in high group [24]. In this study, all of fasting plasma glucose, blood pressure, HDL-C, plasma triglyceride, and waist circumference in high group were much higher than those in low group.…”
Section: Discussionmentioning
confidence: 99%